The Neurobiology and Psychology of Pedophilia: Recent Advances and Challenges - Tenbergen, Gilian; Wittfoth, Matthias; Frieling, Helge; Ponseti, Jorge; Walter, Martin; Walter, Henrik; Beier, Klaus M.; Schiffer, Boris; Kruger, Tillmann H. C. (Frontiers in Human Neuroscience, 2015)
A pedophilic disorder is recognized for its impairment to the individual and for the harm it may cause others. Pedophilia is often considered a side issue and research into the nature of pedophilia is delayed in comparison to research into other psychiatric disorders. However, with the increasing use of neuroimaging techniques, such as functional and structural Magnetic Resonance Imaging (sMRI, fMRI) together with neuropsychological studies we are increasing our knowledge of predisposing and accompanying factors contributing to pedophilia development. At the same time we are faced with methodological challenges such as group differences between studies including age, intelligence, and comorbidities together with a lack of careful assessment and control of child sexual abuse. Having this in mind this review highlights the most important studies investigating pedophilia, with a strong emphasis on (neuro-) biological studies, combined with a brief explanation of research into normal human sexuality. We focus on some of the recent theories on the etiology of pedophilia such as the concept of a general neurodevelopmental disorder and/or alterations of structure and function in frontal, temporal and limbic brain areas. With this approach we aim to not only provide an update and overview but also a framework for future research and to address one of the most significant questions of how pedophilia may be explained by neurobiological and developmental alterations.